BOOK REVIEW: TED UNDERWOOD, "DISTANT HORIZONS: DIGITAL EVIDENCE AND LITERARY CHANGE", CHICAGO: UNIVERSITY OF CHICAGO PRESS, 2019, 200 P. - BUCȘEA, Maria (Studia Universitatis Babeș-Bolyai Philologia, 2022)
Could distant reading ever work? Could digital archives and statistical tools deepen our understanding of issues that have always been central to humanistic inquiry? These are the very premises of Ted Underwood’s latest book, Distant Horizons, published in 2021 with University of Chicago Press. This book contains a completely fresh and original approach to literary theory, accessible to both experts and students in the humanities. It shows how digital methods can bring into focus the bigger horizon of literary theory and add to the beauty and complexity we value in literature, as the afterword highlights.